2015
DOI: 10.1016/j.celrep.2015.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages Contribute to the Spermatogonial Niche in the Adult Testis

Abstract: Summary The testis produces sperm throughout the male reproductive lifespan by balancing self-renewal and differentiation of spermatogonial stem cells (SSCs). Part of the SSC niche is thought to lie outside the seminiferous tubules of the testis; however, specific interstitial components of the niche that regulate spermatogonial divisions and differentiation remain undefined. We identified distinct populations of testicular macrophages, one of which lies on the surface of seminiferous tubules in close appositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
282
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(299 citation statements)
references
References 60 publications
15
282
1
1
Order By: Relevance
“…Mature testicular macrophages play an important role in modulation of immune responses by either helping to maintain the immunosuppressive environment of the testis or stimulating the immune response through secretion of anti-inflammatory or proinflammatory cytokines, respectively [69,70]. Moreover, a distinct class of testicular macrophages that are enriched near spermatogonial precursors and are required for spermatogonia differentiation has recently been identified [46]. An increase in macrophage population and macrophage-stimulated neovascularization are a part of typical inflammatory response [71,72].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mature testicular macrophages play an important role in modulation of immune responses by either helping to maintain the immunosuppressive environment of the testis or stimulating the immune response through secretion of anti-inflammatory or proinflammatory cytokines, respectively [69,70]. Moreover, a distinct class of testicular macrophages that are enriched near spermatogonial precursors and are required for spermatogonia differentiation has recently been identified [46]. An increase in macrophage population and macrophage-stimulated neovascularization are a part of typical inflammatory response [71,72].…”
Section: Discussionmentioning
confidence: 99%
“…During development, they help to establish testicular architecture by promoting male-specific vascularization patterns and testis cord morphogenesis [62,63]. By birth and into adulthood, testicular macrophages are present only in the interstitial compartment of the testes [46,64] where they contribute to cellular maintenance of the immunoprivileged testis and are associated with the steroidogenic Leydig cells [65][66][67][68]. Mature testicular macrophages play an important role in modulation of immune responses by either helping to maintain the immunosuppressive environment of the testis or stimulating the immune response through secretion of anti-inflammatory or proinflammatory cytokines, respectively [69,70].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have demonstrated that testicular RA mainly originates from Sertoli cells especially in puberty; however, it remains elusive whether the action of RA on spermatogonial differentiation is through germ cells or Sertoli cells, or both Sertoli and germ cells, as its receptors, RARs and RXRs, are expressed in both Sertoli cells and the undifferentiated spermatogonia (Gely-Pernot et al, 2012;Tong et al, 2013;Vernet et al, 2006b;Gaemers et al, 1998;DeFalco et al, 2015). For instance, genetic ablation of Rarg in germ cells resulted in only mild spermatogonial differentiation defects in mutants younger than one year old, indicating that either retinoid signaling in Sertoli cells is involved in spermatogonial differentiation, or that other subtypes of RARs in spermatogonia compensate for loss of RARÎł function, as it is the case for many other developmental process (Gely-Pernot et al, 2012;Mark et al, 2009).…”
Section: Discussion Retinoid Signaling Directly Controls Spermatogonimentioning
confidence: 99%
“…In this study, we used Laminin in combination with differentiating plating (DP) method to isolate SSCs from postnatal porcine testicular cells. Niche and microenvironments play important roles in the fate and behavior of stem cells (Griswold et al 2013;DeFalco et al 2015). Recent studies demonstrate the importance of growth factors and extracellular matrix (ECM) on stem cell and germ cell behavior (Kuijk et al 2009;Zhu et al 2012).…”
Section: Discussionmentioning
confidence: 99%